Pengaturan Jabatan Rangkap Anggota Direksi dan Dewan Komisaris BUMN: Perbandingan Indonesia dengan Amerika Serikat - Putra Adibil Anam; Inda Rahadiyan (Jurnal Hukum IUS QUIA IUSTUM, 2023)
This research aims to identify the comparison between the arrangements for interlocking directorates or dual positions of Directors and Commissioners of BUMN in Indonesia and the United States. This is because the two countries have different arrangements and approaches to proof. The problem formulation in this research is how interlocking directorates are regulated in the United States, and how the interlocking directorate arrangements for Directors and Commissioners of BUMN in Indonesia compare with the United States. This is normative legal research with statutory, conceptual, and comparative approaches. The results of this research are, first, the legal basis for interlocking directorates in America is regulated in the Clayton Act Section 8, while in Indonesia is regulated in several sectoral laws and implementing regulations. Second, the body authorized to monitor anti-competition in the United States is the FTC, while in Indonesia it is the Supervisory Board for Business Competition (Komisi Pengawas Persaingan Usaha, KPPU). Third, the imposition of sanctions in the United States is civil penalties, while in Indonesia there are administrative sanctions, principal penalties and additional penalties. Fourth, the approach used in the United States is illegal per se, whereas in Indonesia it is the rule of reason. Even though in the Business Competition Law the approach used in multiple positions is the rule of reason, it does not rule out the possibility that the business competition approach can be carried out using an illegal per se approach.Keywords: Arrangement; Comparison; Interlocking Directorates AbstrakPenelitian ini bertujuan untuk mengetahui perbandingan pengaturan interlocking directorates atau jabatan rangkap Direksi dan Komisaris BUMN di Indonesia dengan Amerika Serikat. Hal ini dikarenakan pada kedua negara tersebut memiliki pengaturan dan pendekatan yang berbeda dalam pembuktiannya. Adapun rumusan masalah dalam penelitian ini ialah bagaimana pengaturan interlocking directorates di Amerika Serikat, dan bagaimana perbandingan pengaturan interlocking directorates Direksi dan Komisaris BUMN di Indonesia dengan Amerika Serikat. Jenis penelitian ini ialah hukum normatif dengan metode pendekatan peraturan perundang-undangan, konseptual dan perbandingan. Hasil dari penelitian ini ialah pertama, dasar hukum interlocking directorates di Amerika diatur dalam Clayton Act Section 8, sedangkan di Indonesia diatur pada beberapa undang-undang sektoral dan aturan pelaksananya. Kedua, badan yang berwenang mengawasi anti persaingan di Amerika Serikat adalah FTC, sedangkan di Indonesia adalah KPPU. Ketiga, pemberlakuan sanksi di Amerika Serikat civil penalties, sedangkan di Indonesia sanksi administrasi, pidana pokok dan pidana tambahan. Keempat, pendekatan yang digunakan di Amerika Serikat ialah per se illegal, sedangkan di Indonesia adalah rule of reason. Walaupun dalam UU Persaingan Usaha pendekatan yang digunakan dalam rangkap jabatan ialah rule of reason, namun tidak menutup kemungkinan pendekatan persaingan usaha dapat dilakukan melalui pendekatan per se illegal.Kata kunci: Jabatan Rangkap; Pengaturan; Perbandingan.